Biochar from food processing wastes: a multi-criteria roadmap for circular energy and environmental applications - Soomro, Ahsanullah; Kocer, Anil Tevfik; Balkanli, Didem (SPRINGER HEIDELBERG, 2026)
This review develops a region-specific Multi-Criteria Decision Analysis (MCDA)-based screening framework for evaluating food-processing residues for biochar applications, offering a transparent and replicable decision-support tool for policymakers and bioeconomy stakeholders in Turkey and beyond. Using Turkey as a region-specific case context, ten underutilized residues-boza fermentation residue, tarhana fines, rosehip seed cake, mulberry syrup press-cake, carob syrup pulp residue, pumpkin seed oil cake, saffron floral by-products, fig-jam seed fraction, lupin brining sediment, and date syrup filter cake-were compiled from the literature and characterized in terms of moisture, ash, organic fractions, higher heating value, and macro-mineral composition. Drawing on thermochemical fundamentals, the review synthesizes how these traits influence biochar properties relevant to fuel use, soil amendment, pollutant adsorption, anaerobic digestion (AD) enhancement, and composite materials, and qualitatively links residue groups to suitable conversion windows such as hydrothermal carbonization and low- or high-severity slow pyrolysis. To convert this information into a transparent screening tool, all indicators were normalized via min-max transformation and aggregated into four mechanistic proxies capturing fuel quality, nutrient release, an adsorption-oriented screening proxy, and AD compatibility. A Simple Additive Weighting (SAW) method was then used to calculate 0-1 suitability scores and 0-100 indices for five application domains: fuel, soil amendment, adsorption/remediation, AD enhancement, and composite/material use. Under the selected criteria and weighting assumptions, rosehip seed cake, pumpkin seed oil cake, carob syrup pulp residue, and fig-jam seed fraction emerged as comparatively high-priority feedstocks, whereas saffron floral by-products and lupin brining sediment showed consistently low relative suitability. By linking feedstock chemistry to application-oriented screening scores, the framework supports rapid comparison of residue-to-application pathways while acknowledging that rankings may evolve as additional performance data, logistical constraints, or alternative weighting scenarios are incorporated.
Keywords: Biochar; Pyrolysis; Food-processing residues; Multi-criteria decision analysis (MCDA); Circular bioeconomy; PYROLYSIS TEMPERATURE; CHEMICAL-PROPERTIES; MINERAL CONTENTS; BIOMASS; SOIL; CARBONIZATION; YIELD; REMOVAL; TARHANA; AMELIORATION; Biotechnology & Applied Microbiology